Crohn's Disease Defined in Three Elderly Disters - Hugh J Freeman (Canadian Journal of Gastroenterology)
Three elderly sisters presented with symptomatic Crohn's disease. All had ileocolic involvement, and granulomatous inflammation was documented in endoscopic biopsies or surgically resected intestinal specimens. The present report documents the unusual occurrence of very late phenotypical expression of familial ileocolic Crohn's disease. The observations presented here reflect a possible gene-based predisposition to Crohn's disease or, alternatively, disease clustering related to a commonly shared environmental factor.